The macroeconomics of the labor market: Three fundamental views - Marika Karanassou; Héctor Sala; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2007)
We distinguish and assess three fundamental views of the labor market regarding the movements in unemployment: (i) the frictionless equilibrium view; (ii) the chain reaction theory, or prolonged adjustment view; and (iii) the hysteresis view. While the frictionless view implies a clear compartmentalization between the short- and long-run, the hysteresis view implies that all the short-run fluctuations automatically turn into long-run changes in the unemployment rate. We assert the problems faced by these conceptions in explaining the diversity of labor market experiences across the OECD labor markets. We argue that the prolonged adjustment view can overcome these problems since it implies that the short, medium, and long runs are interrelated, merging with one another along an intertemporal continuum.
Keywords: E22; E24; J21; J30; 330; Interactive labor market dynamics; Interplay of lags and shocks; Frictional growth; Growth drivers; Unemployment; Theorie der Arbeitslosigkeit; Arbeitsmarkt; Theorie; OECD-Staaten